Runx3 regulates iron metabolism via modulation of BMP signalling. (6th October 2021) - Kim, Hyun‐Yi; Lee, Jong‐Min; Lee, You‐Soub; Li, Shujin; Lee, Seung‐Jun; Bae, Suk‐Chul; Jung, Han‐Sung
Abstract: Objectives: Runx3, a member of the Runx family of transcription factors, has been studied as a tumour suppressor and key player of organ development. In a previous study, we reported differentiation failure and excessive angiogenesis in the liver of Runx3  knock‐out (KO) mice. Here, we examined a function of the Runx3 in liver, especially in iron metabolism. Methods: We performed histological and immunohistological analyses of the Runx3  KO mouse liver. RNA‐sequencing analyses were performed on primary hepatocytes isolated from Runx3 conditional KO (cKO) mice. The effect of Runx3  knock‐down (KD) was also investigated using siRNA‐mediated KD in functional human hepatocytes and human hepatocellular carcinoma cells. Result: We observed an iron‐overloaded liver with decreased expression of hepcidin in Runx3  KO mice. Expression of BMP6, a regulator of hepcidin transcription, and activity of the BMP pathway were decreased in the liver tissue of Runx3  KO mice. Transcriptome analysis on primary hepatocytes isolated from Runx3 cKO mice also revealed that iron‐induced increase in BMP6 was mediated by Runx3. Similar results were observed in Runx3  knock‐down experiments using HepaRG cells and HepG2 cells. Finally, we showed that Runx3 enhanced the activity of the BMP6 promoter by responding to iron stimuli in the hepatocytes. Conclusion: In conclusion, we suggest that Runx3 plays important roles in iron metabolism of the liver through regulation of BMP signalling. Abstract : The increasing body iron stimulates the production of BMP6, which binds to a complex of type I and II BMP receptors on the plasma membrane of hepatocytes. This leads to the phosphorylation of SMAD1, 5 and 8 in the cytoplasm, which allows the binding of SMAD4. The entire complex is then translocated into the nucleus where it binds to BMP responsive elements in the hepcidin promoter, stimulating transcription. However, the regulation mechanism of BMP6 by iron stimuli has not yet been revealed. Here, we showed that Runx3  KO or KD in mouse primary hepatocytes, human hepatocytes and human hepatocarcinoma decreased BMP6 expression and inhibited the BMP‐Smad pathway in human hepatocytes. Therefore, Runx3 regulates iron metabolism of the liver via modulation of BMP signaling.